Icon for the treatment of postorthodontic white spot lesions - Resende, Leonardo Diniz; Bresciani, Eduardo [UNESP]; Rocha, Rafael dos Santos [UNESP]; Sendyk, Wilson Roberto; Kim, Yeon Jung; Pallos, Debora (My University, 2024)
The objective of the present case report is to describe Icon resin infiltration as a treatment option for postorthodontic white spot lesions (WSls). A 23-year-old male patient complained of white spots on his maxillary anterior teeth that caused him significant esthetic concern in terms of his smile and affected his self-esteem. During the anamnesis, the patient reported that he noticed white spots directly after the brackets were removed after orthodontic treatment, which had not yet been completed. based on the information obtained through the anamnesis and the clinical examination, the spots were deemed to be remineralized WSls. The proposed treatment consisted of supervised at-home tooth whitening through bleaching in combination with microabrasion and resin infiltration. The clinical results were successful, showing significant improvement in terms of esthetics and the patient’s self-esteem after only a single session of resin infiltration with Icon material. Treatment optimization and gain in clinical time were clearly demonstrated as well as the preservation of tooth tissue compared with other treatments.
Keywords: Icon; orthodontic treatment; resin infiltration technique; white spot lesions